THE INFLUENCE OF SOCIAL MEDIA MARKETING AND ONLINE CONSUMER BEHAVIOR IN THE CITY OF SUBANG ON THE BRAND STORY OF THE INSTANT MESSENGER LINE APPLICATION - Nunik Ratnasari; Gugyh Susandy; Devy Widya Apriandi (STIESA Press, 2019)
The purpose of this study was to determine the effect of social media marketing and online consumer behavior to brand story on instant messenger Line application. The research method is explanatory survey. The sample selection is done by purposive sampling with the number of samples study were 100 respondents. The data used are interval data. The statistic method used for the test data performed using SPSS 20 for Windows. The survey results revealed that social media marketing have a significant effect on brand story. Online consumer behavior have a significant effect on brand story. As well as social media marketing and online consumer behavior simultaneously have a significant effect on brand story. The coefficient of determination of 42% means that social media marketing and online consumer behavior affect a brand story by 42% and 58% were influenced by other factors.